FUNDAMNTALS OF EDUCATIONAL MULTICULTURALISM IN GREAT BRITAIN - Ковалинська, Інна Володимирівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The aim of the аrticle is to describe the legislative fundamentals of educational multiculturalism in Great Britain. The article provides a survey of basic law papers that present the judicial support of multicultural educational system formation in the country. The author underlines that the multicultural educational system in Great Britain was created thanks to a well-reasoned policy of the government and implementation of a number of acts that constitute the institutional component of multicultural educational system. These papers determined the status of the UK as a multinational country, also described the rights and privileges of immigrants, as well as pointed out the aims and tasks of educational policy in a multinational country. Implementation of these documents provided a legal background for a number of governmental and non-governmental agencies to start their activities, the target of such organizations was to provide equal opportunities in education to all, which corresponds to principles of European democracy